An Evolutionary Model Encompassing Substrate Specificity and Reactivity of Type I Polyketide Synthase Thioesterases. Issue 18 (29th October 2014) - Hari, Taylor P. A.; Labana, Puneet; Boileau, Meaghan; Boddy, Christopher N.
Abstract Bacterial polyketides are a rich source of chemical diversity and pharmaceutical agents. Understanding the biochemical basis for their biosynthesis and the evolutionary driving force leading to this diversity is essential to take advantage of the enzymes as biocatalysts and to access new chemical diversity for drug discovery. Biochemical characterization of the thioesterase (TE) responsible for 6‐deoxyerythronolide macrocyclization shows that a small, evolutionarily accessible change to the substrate can increase the chemical diversity of products, including macrodiolide formation. We propose an evolutionary model in which TEs are by nature non‐selective for the type of chemistry they catalyze, producing a range of metabolites. As one metabolite becomes essential for improving fitness in a particular environment, the TE evolves to enrich for that corresponding reactivity. This hypothesis is supported by our phylogenetic analysis, showing convergent evolution of macrodiolide‐forming TEs.